SPE International Symposium and Exhibition on Formation Damage Control 2014
DOI: 10.2118/168137-ms
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Plugged Asphaltene in a Reservoir by Earthquakes

Abstract: This paper provides a phenomenological description of a positive correlation between earthquakes and improvement of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A relationship exists between the impacts propagated by earthquakes and those by ultrasonic waves, in which both produce vibration effects. Uetani et al [44] proposed a relationship between the occurrence of earthquakes and improvement of asphaltene problems in a Japanese oil field study. In their study, the particular field had shown serious formation damage by asphaltene deposition that reduced the production rates in two wells.…”
Section: Field Studiesmentioning
confidence: 99%
“…A relationship exists between the impacts propagated by earthquakes and those by ultrasonic waves, in which both produce vibration effects. Uetani et al [44] proposed a relationship between the occurrence of earthquakes and improvement of asphaltene problems in a Japanese oil field study. In their study, the particular field had shown serious formation damage by asphaltene deposition that reduced the production rates in two wells.…”
Section: Field Studiesmentioning
confidence: 99%